Stop motion masculinity. Issue 1 (9th August 2012) - Shaw, Nathan
Since the mid-2000s Romanian cinema has, on all levels, been gripped by a new wave characterized by austerity, unflinching realism and a bleak, deeply metaphoric mise-en-scène. This is a style that is both prevalent in and enhanced by the exhibition of masculinity in crisis as shown in The Cage.